New solid-state onload tap-changers topology for distribution transformers. - Faiz, J. (IEEE Transactions on power delivery)
High controllability advantages of power electronic switches lead to their application in the tap-changer of distribution transformers. Using such switches leads to quick operation of the tap-changer and, thus, improved performance. Moreover, their application reduces maintenance and repair costs of tap-changers. This paper introduces a new solid-state onload tap-changer topology that has many steps with fewer power electronic switches compared with those reported in the literature. This tap-changer is designed for an 800-kVA, 20-kV/400-V distribution transformer, and the results are discussed.